KEY PROBLEMS OF INTERACTION BETWEEN ORGANIZATIONS IN IMPLEMENTATION JOINT PROJECTS ON RESEARCH AND DEVELOPMENT - Yu. Kafiyatullina; E. Panfilova (Вестник университета)
Innovative activity of domestic organizations continues to remain low: from 2014 to 2016, there was a reduction in the cost of technological innovations, organizations prefer to import foreign equipment in order to increase the innovation component of the products sold. The way out of the situation is to conduct joint research and development projects, according to the results of which Russian organizations will have the rights to advanced development, acquire competitive competences, which will later allow our country to reduce the technological gap. The article analyzes the current state of research and development, innovation activity, the level of development of digital technologies in our country, which allows to outline the range of problems that hinder the effective implementation of joint research and development projects.